Addressing certain issues of administrative and legal regulation of liability for violation of legal requirements for the safety of vehicle operation in Ukraine - O. M. Halkina; A. O. Ivanov (Bulletin of Kharkiv National University of Internal Affairs)
Unfortunately, the state of law and order on the roads of Ukraine is extremely disappointing, and the sad statistics of road accidents and people injured in them are quite convincing. It is clear that this situation is not normal and poses a threat to individuals, including Ukrainian citizens, as well as to the public and state interests in general. The urgency and importance of road safety issues is emphasised by both academics and the official authorities, who have a strategic vision of the key issues in this area and ways to address them. However, despite this, no significant positive results have been achieved so far.